Crop evapotranspiration assessment under climate change in the Pannonian basin during 1991–2050. (January 2017) - Nistor, Mărgărit‐Mircea; Cheval, Sorin; Gualtieri, Alessandro F.; Dumitrescu, Alexandru; Boţan, Vanessa E.; Berni, Alex; Hognogi, Gheorghe; Irimuş, Ioan A.; Porumb‐Ghiurco, Cosmin G.
ABSTRACT: The impact of climate on crop evapotranspiration (ETc ) was assessed in the Pannonian basin for the present (1991–2020) and future (2021–2050). Annual temperature, annual precipitation and monthly potential evapotranspiration are the main climate data used in the present study. The European land cover database was used for the spatial recognition of terrain vegetation of the countries which are found in the Pannonian basin. A difference of maximum annual temperature from 19.9 to 20.8 °C was observed in the investigated area between 1991–2020 and 2021–2050. Precipitation rates decrease from west (1800 mm) to east (below 400 mm), and the potential evapotranspiration varies from 500 to 800 mm. Four stages of crop growth were identified and for each stage the crop co‐efficients were assessed. For present projections of climate data, the annual crop evapotranspiration variability is from 105 to 1087 mm and records the highest values in mid‐season stage, over 630 mm. Future projections indicate that in the central and southern part of the Pannonian basin the annual crop evapotranspiration will increase. For both present and future projections, the lowest crop evapotranspiration was found in the cold season, because of lack of heat and lower values of the crop co‐efficient.